2013
DOI: 10.1371/journal.pone.0076967
|View full text |Cite
|
Sign up to set email alerts
|

Association of 5-Methylcytosine and 5-Hydroxymethylcytosine with Mitochondrial DNA Content and Clinical and Biochemical Parameters in Hepatocellular Carcinoma

Abstract: Increasing epidemiological evidence has indicated that inherited variations of mitochondrial DNA (mtDNA) copy number affect the genetic susceptibility of many malignancies in a tumour-specific manner and that DNA methylation also plays an important role in controlling gene expression during the differentiation and development of hepatocellular carcinoma (HCC). Our previous study demonstrated that HCC tissues showed a lower 5-hydroxymethylcytosine (5-hmC) content when compared to tumour-adjacent tissues, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…[ 29 ] The present study revealed that 5mC immunohistochemical expression is significantly lower in adenomas measuring 1 cm or more, and those with severe dysplastic change. The mean value of 5mC was inversely correlated with increasing morphologic dysplasia in adenomas (mild, moderate, and severe), which is comparable with a recent study conducted by Shen et al[ 30 ] There was no significant difference in 5mC immunohistochemical expression according to histopathological types of adenomas (tubular, villous, and tubulovillous) and other clinicopathological parameters, including age, gender, and site, which agrees with a previous study by Bariol et al[ 22 ]…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[ 29 ] The present study revealed that 5mC immunohistochemical expression is significantly lower in adenomas measuring 1 cm or more, and those with severe dysplastic change. The mean value of 5mC was inversely correlated with increasing morphologic dysplasia in adenomas (mild, moderate, and severe), which is comparable with a recent study conducted by Shen et al[ 30 ] There was no significant difference in 5mC immunohistochemical expression according to histopathological types of adenomas (tubular, villous, and tubulovillous) and other clinicopathological parameters, including age, gender, and site, which agrees with a previous study by Bariol et al[ 22 ]…”
Section: Discussionsupporting
confidence: 91%
“…The present research reported nonsignificant correlation between 5mC immunohistochemical expression with age, gender, site grade, and histopathological types of colorectal carcinoma; this is equivalent with other studies. [ 22 30 ] There was significant correlation between 5mC immunohistochemical expression with stage of carcinoma, which agrees with recent articles. [ 30 32 ]…”
Section: Discussionsupporting
confidence: 90%
“…At present it is not known whether mtDNA methylation is subjected to reprogramming during embryogenesis as nDNA. However, the dynamic mtDNA methylation patterns associated with aging (17), environmental stimuli (13,87), and diseases (45,84) highlight the possibility that remodeling of mtDNA methylation could occur through a rapid methylation/ demethylation turnover. This is also supported by very interesting findings on the role of pharmaceuticals such as valproic acid in modulating mitochondrial epigenetics (18).…”
Section: Dna Methylation Turnover: Methyl Vs Hydroxymethylcytosinementioning
confidence: 99%
“…Determination of mtDNA copy numbers and GSTK1 expression A quantitative polymerase chain reaction (qPCR) that simultaneously targeted a single-copy nuclear gene (b2microglobulin, b 2 M) and the tRNA Leu (UUR) gene on the mtDNA was used to quantify mtDNA copy numbers [12][13][14]. GSTK1 expression (mRNA) was quantified and normalized by b-ACTIN and GAPDH.…”
Section: Plasma Nucleic Acid Extractionmentioning
confidence: 99%